‘New Regionalism’: ASEAN – RoK partnership in socio-cultural and education exchanges - Ahmad Rosland, Nur Nazifah (AEI Insights, 2021)
ASEAN and South Korea have achieved substantial progress in political and economic relationship since 1989, when they first established a dialogue partnership. In 2010, their relationship further developed into a ‘Strategic Partnership in Peace and Prosperity’. ASEAN and South Korea share a common interest in promoting peace, stability, and prosperity in the region and beyond. ‘New regionalism’ theory has become current interest in regionalism and is undoubtedly one of the important trends in contemporary international relations. This theory focuses more on ‘deep integration’ between countries. ASEAN and South Korea emerged from the same root of colonization and escalated to become the second largest trading partner with its relationship thriving in tourism and educational sector. In this study, I focus on the development of ‘new regionalism’ in ASEAN and Republic of South Korea partnership as well as their regional integration efforts in the area of socio-culture and education. The study contributes to the existing knowledge of regionalism between ASEAN-Korea; the mutual relationship which emerged from economic and political-security into the area of socio-culture and education.